Local Convergence of Jarratt-Type Methods with Less Computation of Inversion Under Weak Conditions - Argyros, Ioannis K.; George, Santhosh (Mathematical Modelling and Analysis, 2017)
We present a local convergence analysis for Jarratt-type methods in order to approximate a solution of a nonlinear equation in a Banach space setting. Earlier studies cannot be used to solve equations using such methods. The convergence ball and error estimates are given for these methods. Numerical examples are also provided in this study.